2020
DOI: 10.1016/j.jmbbm.2020.103858
|View full text |Cite
|
Sign up to set email alerts
|

3D full-field strain in bone-implant and bone-tooth constructs and their morphological influential factors

Abstract: The biomechanics of bone-tooth and bone-implant interfaces affects the outcomes of several dental treatments, such as implant placement, because bone, tooth and periodontal ligament are living tissues that adapt to the changes in mechanical stimulations. In this work, mechanical testing coupled with micro-CT was performed on human cadaveric mandibular bone-tooth and bone-implant constructs. Using digital volume correlation, the 3D full-field strain in bone under implant loading and tooth loading was measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
(76 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, Palamara et al [ 13 ] found that both the magnitude and the orientation of strains would change at the CEJ, which might contribute to NCCLs. The phenomenon of changes in the magnitude of strains at the CEJ has been observed in previous experiments [ 16 , 20 ]; hence, it was the aim of this study to observe whether the orientations of strains at the CEJ change under occlusal forces in in vitro conditions to further verify the hypothesis put forward by Palamara et al [ 30 ] on the basis of FEA. The null hypothesis was that the orientations of strains at the CEJ would remain constant under occlusal forces.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Furthermore, Palamara et al [ 13 ] found that both the magnitude and the orientation of strains would change at the CEJ, which might contribute to NCCLs. The phenomenon of changes in the magnitude of strains at the CEJ has been observed in previous experiments [ 16 , 20 ]; hence, it was the aim of this study to observe whether the orientations of strains at the CEJ change under occlusal forces in in vitro conditions to further verify the hypothesis put forward by Palamara et al [ 30 ] on the basis of FEA. The null hypothesis was that the orientations of strains at the CEJ would remain constant under occlusal forces.…”
Section: Introductionmentioning
confidence: 60%
“…Pointwise measurements, such as those provided by strain gauges [ 6 ], are sometimes not sufficient to fully monitor an experiment. Bioengineering tools [ 7 ] such as finite elements analysis (FEA) [ 8 , 9 , 10 , 11 , 12 , 13 ], moiré interferometry (MI) [ 14 , 15 , 16 , 17 ], electronic speckle pattern interferometry (ESPI) [ 18 , 19 , 20 , 21 ], and DIC [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have been widely used in studying the mechanics of tooth or dental material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between clinical stability (evaluated by ISQ values) and the biological events pertinent to the documented phase has been shown in relevant studies. 1821 The results of Zhou et al 15 showed a strong linear relationship between the results of the torque test and RFA, while some studies pointed out that the correlation between torque value and ISQ was not statistically significant. 22,23…”
Section: Introductionmentioning
confidence: 96%
“…Implant stability is a prerequisite for successful implantation procedure and long-term positive outcomes of dental implants. 13,14 Many influential investigations have been conducted to measure implant stability by clinical methods, including torque test, 15 periotest, 16 resonance frequency analysis (RFA), 4,16 and pull-out strengths (POS). 4 Periotest can be measured at the time of implant insertion for complimentary assessment during the osseointegration period.…”
Section: Introductionmentioning
confidence: 99%